Sex and the flower – developmental aspects of sex chromosome evolution. (18th July 2018) - Hobza, Roman; Hudzieczek, Vojtech; Kubat, Zdenek; Cegan, Radim; Vyskot, Boris; Kejnovsky, Eduard; Janousek, Bohuslav
Abstract: Background: The evolution of dioecious plants is occasionally accompanied by the establishment of sex chromosomes: both XY and ZW systems have been found in plants. Structural studies of sex chromosomes are now being followed up by functional studies that are gradually shedding light on the specific genetic and epigenetic processes that shape the development of separate sexes in plants. Scope: This review describes sex determination diversity in plants and the genetic background of dioecy, summarizes recent progress in the investigation of both classical and emerging model dioecious plants and discusses novel findings. The advantages of interspecies hybrids in studies focused on sex determination and the role of epigenetic processes in sexual development are also overviewed. Conclusions: We integrate the genic, genomic and epigenetic levels of sex determination and stress the impact of sex chromosome evolution on structural and functional aspects of plant sexual development. We also discuss the impact of dioecy and sex chromosomes on genome structure and expression.